Assessment of Reading Habits of Public Library Users in the Digital Era: An Empirical Study - Halder, Sambhu Nath (Journal of Information and Knowledge, 2021)
In the Context of rapid increase in electronic resources the reading habits of the public library user community are examined. A representative sample was drawn from a large and heterogeneous population following a stratified sampling technique. The reading habits of the users were identified using several parameters adopted to achieve the objectives of the study. Findings of the study revealed that 41.82% of respondents visit the library 2-4 times per month, followed by 22.05% used to visit it 2-3 times per week, while only 16.82% of the respondents visit the library almost regularly. However, the study indicated that electronic documents have an important role in enhancing people’s reading habits. It is recommended that the library needs to emphasize on collecting both printed as well as digital resources. While reading habits of public library users are stable, they were quite comfortable reading in a digital environment.